IMPLEMENTASI PENGELOLAAN SUMBER DAYA PESISIR BERBASIS PENGELOLAAN WILAYAH PESISIR SECARA TERPADU UNTUK KESEJAHTERAAN NELAYAN (STUDI DI PERDESAAN NELAYAN CANGKOL KELURAHAN LEMAHWUNGKUK KECAMATAN LEMAHWUNGKUK KOTA CIREBON) - Endang Sutrisno (Faculty of Law, Universitas Jenderal Soedirman, 2014)
Coastal zone management in local area, especially in Cirebon has a deep tendency to be partial, the policies issued are not well-integrated among the sectors. Meanwhile, in the other hand, the im-plementation of policies are not support by the culture of fishing communities which apathetic. It is caused by various factors such as poverty, poor education in the community, less mastery of science and technology, as well as the marketing of fishery products trade system which is dominated by middlemen. This factual circumstance makes them difficult to realize their independence and well-being. The most appropriate solution to overcome this problem is through development of positive and creative legal culture, with the support of integrated coastal zone management policy that is integral-holistic-comprehensive. Key words: development, fishermen, management and law